Qualitative research a guide to design and implementation - Merriam, Sharan B.; Tisdell, Elizabeth J. (Jossey-Bass higher and adult education series, 2016)
This thoroughly revised and updated classic once again presents a guide to understanding, designing and conducting a qualitative research study. The fourth edition retains the reader-friendly, jargon-free style, making the book accessible to both novice and experienced researchers. While the book is practical guide to design and implementation of a qualitative research study, it also helps readers understand the theoretical and philosophical underpinnings of this research paradigm. Drawing on the latest literature as well as both authors' experience with conducting and teaching qualitative research, the fourth edition includes new material on case study research and action research; discussion of online data sources (video, email, Skype); updated discussion of data analysis software packages and uses; new discussion of data analysis strategies, including narrative analysis and poetic analysis; and a section on multiple ways of presenting qualitative research findings. References, examples, and quotes have all been updated throughout the book.